Can Data-Driven Hypotheses Replace the Scientific Method? - Raúl Isea (Journal of Big Data Research, 2023)
The rapid growth of data and scientific journals has led to the promotion of data-based hypotheses. Data-driven hypotheses can also be used to establish new scientific laws or confirm existing ones, demonstrating the foundation of this philosophy. To introduce this idea, this article presents a Python-based computational algorithm that can generate system dynamics equations without using working hypotheses.
Keywords: Data driven Hypothesis